(untitled) (Medical Forum Monthly, 2024)
Objective: The comparison of pin tract infection rate between burried K-wire fixation and subcutaneous K-wire fixation in supra condylar fracture of humerus in children. Study Design: Prospective study. Place and Duration of Study: This study was conducted at the Department of Orthopedic Unit Sir Ganga Ram Hospital Lahore from January 2019 to June 2019. Materials and Methods: Children up to 14 years of age admitted to orthopedic unit of study institution during study period having supra condylar fracture of humerus (Gartland type-3) not more than 3 days old were included in this study. These cases were divided into two groups Group-A & Group-B. Open or closed reduction of fracture using K-wires were done in all cases but wires were buried in cases of group-A and wires were kept percutaneous in group-B. Rate of pin tract infection was seen in both groups on follow-up and compared with each other. All data was recorded on a predesigned performa and analyzed on statistical software SPSS (version 20) and Microsoft office (version 2017). Results: There were total 169 cases in our study divided into two groups group-A (N=79) and group-B (N=90). Mean age of patients was 6.5 years. Out of 79 cases with buried k-wires 1.3% cases developed pin tract infection and out of 90 cases with percutaneous k-wires 6.6% cases developed pin tract infection having statistically significant difference with p-value <0.005. Other complications related to surgical wound were also observed such as hypersensitivity of scar tissue seen in 1 case, ulnar nerve palsy in 3 cases, loosening of k-wires in 3 cases, retrograde migration of wires in 1 cases, tendinitis in 2 cases and osteomyelitis was reported in one case. Mean time of hospital stay after operation was 3±1 days. Mean time of union was 4.5 weeks (3-7 weeks). Conclusion: Our study concluded that among patients with fixation of supra condylar fracture humerus with percutaneous exposed kirschner wires (k-wires) rate of pin tract infection was much higher than buried k-wires and second surgery may be needed to remove infected wires that is a burden on the patient and doctor as well with increased morbidity. Among patients with buried k-wires second surgery is must to remove it after fracture healing but pin tract infection rate is much low.